DENTISTS VIEW ON FETAL MACROSOMIA - Garmash, O.V. (World of Medicine and Biology, 2018)
The article is devoted to the study of the dental status features, including the terms of the deciduous tooth eruption, in the children of Kharkiv population (Kharkiv city, Ukraine) who were born with macrosomia, taking into account accelerated intrauterine growth, intrauterine obesity or balanced intrauterine growth acceleration and the body weight gain. Dental status analysis in newborns and infants born with macrosomia (Main group) and normosomia (Reference group) was carried out. The total of 173 children (102 boys and 71 girls) born in 2014-2017 were examined. It was shown that dental disorders were found in the both groups at birth - in 53.8% of newborns in the macrosomic group and in 24.6% of newborns in the group of normosomes. Abnormalities of soft tissues were associated with fetal macrosomia. In the macrosomic group, in children with the balanced intrauterine increase in body weight and body length, the process of deciduous tooth eruption was more harmonious. Delayed terms of deciduous tooth eruption were observed in children born with macrosomia with enlarged intrauterine body length and relatively low body weight. Children born with macrosomia and intrauterine obesity and girls with intrauterine acceleration in combination with obesity tend to premature tooth eruption. Macrosomic children with large intrauterine body length and a relatively low body weight demonstrated the highest percentage of the violation in tooth eruption sequence and the highest percentage of the bilateral asymmetry.